Innovations in intelligent machines -3 contemporary achievements in intelligent systems - Jordanov, Ivan (Studies in computational intelligence, 2013)
This book aims to promote a sample of current theoretical and application oriented intelligent systems research specifically in the field of neural networks computing. It presents examples of experimental and real-world investigations that demonstrate contemporary achievements and advances in the area of intelligent systems.   This book will prove as a valuable source of up-to-date theoretical and application oriented research in intelligent systems for researchers and postgraduate students.  .